Eksplanatori dan Konfirmatori Hidup sebagai Manusia Baru berdasarkan Kolose 3 : 5 -17 bagi Peserta Didik Kelas 3-6 di SD Bopkri Gunung Ijo dan SD Kristen Widodo Plampang Kulon Progo Yogyakarta Tahun Pelajaran 2024/2025 - Oktavia, Elisha (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to determine the level of Confirmation of Life as a New Man based on Colossians 3:5-17 in grades 3-6 at BOPKRI Gunung Ijo Elementary School and Widodo Plampang Christian Elementary School, Kulon Progo, Yogyakarta, in the 2024/2025 academic year. The method used is quantitative with a survey approach using a validated questionnaire instrument. The research sample included all 26 students from grades III to VI. Data were analyzed using descriptive statistical analysis and linear regression. The results showed that the level of Confirmation of Life as a New Man was in the moderate category with a confidence interval value between 123.47 and 129.30 at a significance level of 5%. In addition, the most dominant dimension in determining the Confirmation of Life was Life in Repentance with an influence of 0.921 and a contribution of 84.8%, while the hypothesis that proposed the dimension of New Life as God's Chosen People was rejected. These findings indicate the importance of the aspect of repentance in the process of forming a new life in students in accordance with the values in Colossians 3:5-17.